THE CONCEPT OF LENIENCY IN REPUBLIC OF NORTH MACEDONIA (EU and comparative law issues and challenges series (ECLIC), 2021)
The concept of "leniency" in competition law, or better known as the "leniency programme", has proven to be an extremely important instrument in fighting unfair competition. In the Republic of Northern Macedonia (hereinafter RNM), this concept of suppressing or reducing unfair competition, more or less, exists solely as a law conception. Nowadays, when the EU discusses the impact of the global crisis and the Coronavirus pandemic on the level of utilization of ”leniency programme", this concept is still unknown or not a well-known concept for business sector in RNM. The main focus of this article is “leniency programme” in RNM. The key questions that we aim to answer here, are: whether and to what extent this instrument is predicted in Macedonian competition law? Is it predicted only as a law category, or it has practical implications too? Although this research refers to RNM, we strongly believe that a thorough study of “leniency” requires exploration of European conception of “leniency” too. For that purpose, we use relevant EU legislation, as well as practice. Thus, our main goal is to consider the position of RNM towards “leniency” and bring into relation to the Macedonian competition law. We base our hypothetical framework on the assumption that the applicability of “leniency programme” in RNM is at the lowest level. Furthermore, that the undertakings are not interested in applying “leniency”. This situation is partly due to the lack of information, the complexity of the application procedure, as well as other factors that are related not only to the attitude of the executive of undertakings, but more to the general economic circumstances, economic development, the market size of goods and services, etc. Using the analytical-descriptive method, the comparative method, and the method of analysis and synthesis, we’ll elaborate the situation in RNM regarding this issue, and we will present our views considering the questions: whether certain measures should be taken regarding „leniency program“, and what should be done to boost the use of this program in the Macedonian business sector.